The Implementation of Omotenashi and Experience of Internship Students in Hotel and Ryokan in Japan - Cicilia Tantri Suryawati; Isnin Ainie; Ni Nyoman Sarmi; Amirul Mustofa; Rommel Utungga Pasopati (Vocational College of Diponegoro University, 2023)
Omotenashi is Japanese hospitability that underlines matter of comfort and satisfaction from others. The best application of omotenashi is in hotel and ryokan in Japan. Some of UNITOMO students did internships on hotel and ryokan in Japan and experienced omotenashi either. This paper aims to explain implementation of omotenashi and reactions of internship students towards standardized omotenashi in hotels and ryokan in Japan. Direct interviews and observations are done to collect the data while qualitative method is used as the way to analyze it. There are three main points needed in doing omotenashi, namely appearance, behavior, and use of language. The main idea is to decorate own self to shape such comfort for others. Internship students realizes standards of omotenashi through various obstacles, especially language, communication, and cultural factors. In conclusion, studying omotenashi is used to understand Japanese hospitality deeper and how it may be applied in hotel and ryokan. Internship students could also deepen knowledge about Japanese discipline in further implementation of omotenashi.